Educational policy in Latin America (Revista Innova Educación, 2021)
The purpose of this work was to know the scientific evidence on educational policy in a systematic review from 2018 to 2020 in Latin America. For it, a review was made according to the PRISMA guidelines of the articles found in the Scopus, Scielo, ProQuest and Ebscohost databases. The results indicate the existence of inequalities in educational policies in the different educational systems, stating that the determining factors are: inclusion and equality, the importance of funding, curriculum foundations and educational curriculum, the educational system from the epistemological point of view and historical, educational policies from the aspect of assessment and its relationship to the curriculum, the use of teaching strategies, democratic consolidation and coexistence school, dialogue and consensus, concentration and participation of educational and social actors actors, rights of free education and quality migrants.
Keywords: Curriculum; pedagogical strategies; evaluation; participation; educational policy